Benefits of incorporating urinary protein/creatinine ratio measurement in a school urine screening system: The experience of restructuring the school urinary screening system in Osaka Prefecture, Japan. Issue 11 (2nd May 2019) - Ashida, Akira; Shoji, Tatsuya; Honda, Shiho; Iio, Rei; Iga, Chihiro; Hayashi, Terumasa; Satomura, Kenichi; Tsubakihara, Yoshiharu
ABSTRACT: Aim: School urine screening has been established in several countries of Asia, including Japan, Korea and Taiwan. In Osaka prefectural schools, the urine screening system had some problematic issues including an unclear referral procedure for students with abnormal urinary findings. Therefore, the school urine screening system was reviewed and restructured in 2004. The aim of this study was to assess the improvement in school urine screening through evaluation of the restructured Osaka prefectural school urinary screening system. Methods: The Osaka prefectural school urinary screening system was reviewed, mainly considering two points. One was the incorporation of standard urinary protein/creatinine ratio measurement instead of the traditional urine dipstick and urine sediment tests; the second point was that all students requiring further examination were referred to regional nephrologists. Results: After restructuring, the number of students who were referred to a medical institute for detailed examinations decreased to 10%, although the number of students newly diagnosed with kidney disease and the types of diagnosis did not change. The positive predictive value of screening increased to about 8 times the value before the system restructuring. The reductions enabled students who required further examination to be referred to regional nephrologists and has contributed to a decreased cost for these examinations. Conclusion: Incorporating urinary protein/creatinine ratio measurement into the school urinary screening system, and updating the guiding principles, including referral to nephrology specialists, has enabled the school urinary screening system in Osaka Prefecture to become more efficient and have better cost performance. SUMMARY AT A GLANCE: Incorporating urinary protein/creatinine ratio measurement into the school urine screening system, and updating the guiding principles, including referral to nephrology specialists, has enabled the school urine screening programme in Osaka Prefecture to become more efficient and have better cost performance.